Describing A Systematic Reflection for Pre-Service Teachers’ Professional Identity: A Case Study - Anastasia Nelladia Cendra; Markus Budiraharjo (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
To fill the gap and add literature on systematic reflections in the area of teacher identity developments, this research, which is a part of a larger case study, described how reflection class followed by pre-service teachers of English language in a teacher development program in Indonesia (PPG Pra-jabatan) was conducted. Using a single case study with embedded design and multiple data sources (observations, interviews, and document analysis), this research found that in its effort to help pre-service teachers' identity development, the reflection class followed a certain procedure that comprises of two phases (i.e. reflection phase and publication preparation phase). In addition, this research also found some protocols that were adhered by the reflection class (i.e. involving social reflection, providing a safe and secure learning environment, feedback provision to the reflections, and giving appropriate prompts). This research recommends the teacher education and teacher professional development programs give more attention to how reflection is conducted. In particular, it is suggested that some protocols of conducting a good reflection are considered so that the pre-service teachers can make the most of the reflective activities.